PENGARUH PEMBERIAN SENAM TAI CHI TERHADAP PENINGKATAN ACTIVITY OF DAILY LIVING PADA LANSIA DIPANTI SOSIAL TRESNA WERDHA KSI BATUSANGKAR TAHUN 2018 - Yemima Miadona N, Reza Olyverdi, (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
The process of growing old must be experienced by everyone in their survival. Where problems related to the development of the life of the elderly one of them is the aging process, both physically, mentally and psychosocially. The older a person, the physical ability will decrease, so that it can lead to a decline in social roles. This also results in the emergence of disruption in terms of fulfilling their needs, so that it can increase dependency which will require the help of others. Based on these guidelines, one of the physical activities that should be recommended for the elderly to exercise their body's functional activities is Tai Chi exercise. This study aims to determine the effect of Tai Chi gymnastic intervention on increasing Activity Of Daily Living in the elderly before and after the Tai chi exercise intervention. This type of research is a quasi-experiment with one group pre-test and post-test design. The measuring instrument for the Activity Of Daily Living used was Index Barthel. The sampling technique was purposive sampling with 10 respondents. Respondents were given Tai Chi exercise for 30 minutes 3 times a week for 2 weeks. Analysis of this research data using the Wilcoxon Signed Ranks Test statistical test. The results of the data analysis test showed that the Activity of Daily Living score of the pre-test was 12.80 and post-test was 15.70 with p-value 0.004. This shows that Tai Chi exercises can increase Activity of Daily Living in the elderly. It can be concluded that Tai Chi gymnastics is one of the right interventions to increase the elderly Activity Of Daily Living at Tresna Werdha Social Institution KSI Batusangkar. It is suggested to the elderly or the surrounding community to always do physical activities, especially Tai Chi exercises that have many benefits, one of which is to increase Activity Of Daily Living Kata Kunci : Senam Tai Chi, Activity Of Daily Living, Lansia